Simple sequence repeat markers that identify Claviceps species and strains. Issue 1 (December 2016) - Gilmore, Barbara; Alderman, Stephen; Knaus, Brian; Bassil, Nahla; Martin, Ruth; Dombrowski, James; Dung, Jeremiah
Abstract Background Claviceps purpurea is a pathogen that infects most members of Pooideae, a subfamily of Poaceae, and causes ergot, a floral disease in which the ovary is replaced with a sclerotium. When the ergot body is accidently consumed by either man or animal in high enough quantities, there is extreme pain, limb loss and sometimes death. Results This study was initiated to develop simple sequence repeat (SSRs) markers for rapid identification of C. purpurea . SSRs were designed from sequence data stored at the National Center for Biotechnology Information database. The study consisted of 74 ergot isolates, from four different host species, Lolium perenne, Poa pratensis, Bromus inermis, andSecale cereale plus three additionalClaviceps species, C. pusilla, C. paspali andC. fusiformis. Samples were collected from six different counties in Oregon and Washington over a 5-year period. Thirty-four SSR markers were selected, which enabled the differentiation of each isolate from one another based solely on their molecular fingerprints. Discriminant analysis of principle components was used to identify four isolate groups, CA Group 1, 2, 3, and 4, for subsequent cluster and molecular variance analyses. CA Group 1 consisting of eight isolates from the host speciesP. pratensis, was separated on the cluster analysis plot from the remaining three groups and this group was later identified asC. humidiphila . The other three groups were distinct from one another, but closely related. These three groups contained samples from all four of the host species. These SSRs are simple to use, reliable and allowed clear differentiation ofC. humidiphila fromC. purpurea . Isolates from the three separate species, C. pusilla, C. paspali andC. fusiformis, also amplified with these markers. Conclusions The SSR markers developed in this study will be helpful in defining the population structure and genetics ofClaviceps strains. They will also provide valuable tools for plant breeders needing to identify resistance in crops or for researchers examining fungal movements across environments.